Meet the Hidden Jesus within you in Javanese spirituality and Namaste greeting - Victor Christianto (The New Perspective in Theology and Religious Studies, 2022)
According to Ted Peters (2018), Public discourse today continues topropagate the simplistic idea that science and religion are engagedin a hopelessly unwinnable war. This is misleading. Science andreligion interact at so many different junctures and in so manydifferent ways that any simple generalization misguides us. Althoughthe present writer wrote several articles on cosmology and logic,actually he is not quite well versed in philosophy, especially to meetthe above tension mentioned by Ted Peters. Nonetheless, we cameup in a converging ideas toward such a dialogue between science,philosophy an and theology. Let me emphasize, that what isoutlined here is not a synthesis or syncretistic idea, but it is meantto be a better dialogical approach, in the sense of Buber. See alsoArion, Hivner (2018, 2011). The present article is a continuation toour three previous articles (Christianto Chandra, 2021; Christianto,Smarandache, Tjandrah Simbolon, 2022; Christianto, 2022), as anintentional discussion of our understanding of classic work, PJ.Zoetmulder, Manunggaling Kawula Gusti. In particular, we discusshow Gospel of Thomas’s place among the other Four Gospels canbe an alternative way to interpret sedulur papat limo pancer as aknown principle held among adherents of Javanese spirituality.